Search for anomalous electroweak production of WW/WZ in association with a high-mass dijet system in pp collisions at s√=8 TeV with the ATLAS detector - Aaboud, M. (2016)
A search is presented for anomalous quartic gauge boson couplings in vector-boson scattering. The data for the analysis correspond to 20.2 fb − 1 of √ s = 8 TeV p p collisions and were collected in 2012 by the ATLAS experiment at the Large Hadron Collider. The search looks for the production of W W or W Z boson pairs accompanied by a high-mass dijet system, with one W decaying leptonically and a W or Z decaying hadronically. The hadronically decaying W / Z is reconstructed as either two small-radius jets or one large-radius jet using jet substructure techniques. Constraints on the anomalous quartic gauge boson coupling parameters α 4 and α 5 are set by fitting the transverse mass of the diboson system, and the resulting 95% confidence intervals are − 0.024 < α 4 < 0.030 and − 0.028 < α 5 < 0.033 .